Fouling study of nanofiltration membranes for sugar control in grape must: Analysis of resistances and the role of osmotic pressure. Issue 3 (11th February 2016) - Salgado, C.; Carmona, F. J.; Palacio, L.; Hernández, A.; Prádanos, P.
ABSTRACT: Three membranes are analyzed attending to their retention, flux, and fouling when used to nanofiltrate sugars in red grape musts. In the presence of high molecular weight compounds, that is, when filtering must, fouling develops from initial pore blocking to final cake deposition. A decrease of resistance appears due to a decrease of the effective transmembrane pressure and cake compaction. The final effective pore size corresponds to that of the compacted cake. Attending to flux decay and sugar retention, two membranes, HL and SR3, are appropriate to reduce the content of sugar of red must. Specifically SR3 shows the best passage of sugar and less fouling.